2020
DOI: 10.3390/ijms21228634
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Methodological Aspects of Cell-Free Nucleic Acids Analyzes

Abstract: Analyzes of cell-free nucleic acids (cfNAs) have shown huge potential in many biomedical applications, gradually entering several fields of research and everyday clinical care. Many biological properties of cfNAs can be informative to gain deeper insights into the function of the organism, such as their different types (DNA, RNAs) and subtypes (gDNA, mtDNA, bacterial DNA, miRNAs, etc.), forms (naked or vesicle bound NAs), fragmentation profiles, sequence composition, epigenetic modifications, and many others. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 328 publications
(306 reference statements)
0
29
0
Order By: Relevance
“…Tubes containing specific preservatives should be used whenever it is not possible to process the sample within 3 h from collection. 11 , 12 …”
Section: Technical Aspectsmentioning
confidence: 99%
“…Tubes containing specific preservatives should be used whenever it is not possible to process the sample within 3 h from collection. 11 , 12 …”
Section: Technical Aspectsmentioning
confidence: 99%
“…Since tumor cells frequently undergo necrosis, they release tumor-specific cfDNA (ctDNA) into body fluids such as blood, urine, saliva, etc. [84]. It was shown that quantification of tumor-specific rearrangements in ctDNA by ddPCR is highly accurate for postsurgical discrimination between patients with an eventual diagnosis of clinical metastasis and long-term disease-free patients, with a sensitivity of 93% (95% CI, 66-100%) and specificity of 100% (95% CI, 61-100%).…”
Section: Potential Biomedical Applications Of Cnv Detectionmentioning
confidence: 99%
“…In addition to sample considerations, there is a need for standardized sampling and processing techniques with respect to liquid profiling of nucleic acids [ 36 , 37 ]. Fortunately, the World Health Organization specifies collection standards for blood and CSF [ 38 , 39 ].…”
Section: Main Textmentioning
confidence: 99%